2007
DOI: 10.1002/hyp.6757
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigation of soil chemical and physical properties associated with type‐I fairy ring symptoms in turfgrass

Abstract: Abstract:Fairy ring is a common disease of turfgrasses worldwide, and necrotic or severely injured turfgrass and soil water repellency are frequently observed in those turfgrass sites exhibiting type-I fairy ring symptoms. The objective of this research was to evaluate soil chemical and physical properties associated with type-I fairy ring symptoms in turfgrass. Soil samples were obtained from type-I fairy ring symptoms on two golf course fairways and one lawn area. Soil analysis from all the three locations r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 17 publications
(19 reference statements)
2
26
0
Order By: Relevance
“…Topdressing and soil surfactant were applied monthly (sand at 3.3 kg m -2 and surfactant at 20 L ha -1 Data are averaged over five sampling depths (0.5, 1.5, 2.5, 3.5, 4.5, and 5.5 cm). also been shown to improve the delivery of some soil-active pesticides such as fairy-ring fungicides (Fidanza et al, 2007a(Fidanza et al, , 2007bFidanza, 2009). Our study documented that turf quality can be maintained at reduced irrigation if either topdressed with a hydrophilic sand or with sand in combination with a surfactant.…”
Section: Soil Hydrophobicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Topdressing and soil surfactant were applied monthly (sand at 3.3 kg m -2 and surfactant at 20 L ha -1 Data are averaged over five sampling depths (0.5, 1.5, 2.5, 3.5, 4.5, and 5.5 cm). also been shown to improve the delivery of some soil-active pesticides such as fairy-ring fungicides (Fidanza et al, 2007a(Fidanza et al, , 2007bFidanza, 2009). Our study documented that turf quality can be maintained at reduced irrigation if either topdressed with a hydrophilic sand or with sand in combination with a surfactant.…”
Section: Soil Hydrophobicitymentioning
confidence: 99%
“…Some of these hydrophobic compounds are exuded by roots (Dekker and Ritsema, 1996;Doerr et al, 1998). Other compounds are produced by microbes, fungi, and even decaying organic matter oft en induced by highly humid conditions (Fidanza et al, 2007a;Jex et al, 1985;McGhie and Posner, 1981;Savage et al, 1972). As a consequence of water repellency, localized dry spots (LDS) can develop and become a signifi cant problem of turfgrass areas.…”
mentioning
confidence: 99%
“…This could be a direct product of pine root and shoot growth and decay or the result of an association between the pine or soil fungus. In turfgrasses, it has been observed that an increase in soil water repellency because of fungus growth in what are called fairy rings (Fidanza et al, 2005;Fidanza et al, 2007). Soil water repellency associated with fairy rings can decrease with soil depths within a few centimeters (0-3-cm deep) in some cases from strongly water repellant to nonrepellent (Fidanza et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In turfgrasses, it has been observed that an increase in soil water repellency because of fungus growth in what are called fairy rings (Fidanza et al, 2005;Fidanza et al, 2007). Soil water repellency associated with fairy rings can decrease with soil depths within a few centimeters (0-3-cm deep) in some cases from strongly water repellant to nonrepellent (Fidanza et al, 2007). In the case of the pine plantation, although the water repellency decreased with soil depths, at 35 cm the soil is moderately hydrophobic for WDPT and slightly hydrophobic at 50 cm for SWA and MED analyses, suggesting that water repellency, at least at deeper depth might be associated to combination of properties in addition to SOC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation